IMPLEMENTASI PENGAWASAN TAHAPAN PEMUTAKHIRAN DATA PEMILIH (DPT) DALAM PEMILU KEPALA DAERAH KOTA MEDAN TAHUN 2010 (STUDI KASUS KELURAHAN PUSAT PASAR KECAMATAN MEDAN KOTA KOTA MEDAN) - David Susanto (PERSPEKTIF, 2016)
The successful implementation of the policy will be determined by many variables or factors, and each of these variables are related to one another. In view of Edwards III, policy implementation is influenced by four variables, namely: (1) communication, (2) resources, (3) disposition, and (4) bureaucratic structure. This research is a descriptive study with a qualitative approach. The results are as follows: (1). Implementation of the discussion using the theory of policy implementation at the stage of monitoring the implementation of data updating voters (DPT) in the city of Medan in 2010 Election not running optimally be seen from the number of people who are not enrolled in the DPT and the limited performance of the Supervisory Committee (2). Inhibiting factors that affect the performance of the Supervisory Committee of Medan in 2010 is a limited member of the Supervisory Committee, the limited time of the establishment (regulation / legislation governing the Supervisory Committee / Election Supervisory Body), HR is not the same (level of education) between Panwas City, District, and Village